Effects of duration of thermal stress on growth performance, serum oxidative stress indices, the expression and localization of ABCG2 and mitochondria ROS production of skeletal muscle, small intestine and immune organs in broilers. (October 2019) - Wang, Juhua; Xue, Xiuheng; Liu, Qi; Zhang, Suzi; Peng, Mengling; Zhou, Jie; Chen, Lijuan; Fang, Fugui
Abstract: The purpose of the current study was to investigate that effect of duration of thermal stress on growth performance, oxidative stress indices in serum, the expression and localization of ABCG2, and mitochondria ROS production in skeletal muscle, small intestine and immune organs, and then to further reveal correlations between indicators. At 28 days of age, sixty broilers were randomly divided into the control group (25 ± 2 °C; 24 h/day) and the heat stress group (36 ± 2 °C; 8 h/day lasted for 1 week or 2 weeks). Fifteen broilers per group were respectively euthanized, and some samples were respectively collected from the control and the heat stress groups at the end of the 1st week or the 2nd week of heat stress. A typical heat stress response has been observed at this temperature. Compared with the control group, the birds subjected to heat stress at the end of the 1st week reduced (P ＜ 0.05) body weight (BW), average daily feed intake (ADFI), average daily gain (ADG), the activity of serum antioxidant enzyme and content of glutathione (GSH), while increased (P ＜ 0.05) feed conversion ratio (FCR), serum corticosterone and malondialdehyde (MDA) levels. However, when the heat stress lasted for the end of the 2nd week, there was no significant difference (P ＞ 0.05) in ADFI, ADG, FCR and serum contents of corticosterone, MDA and GSH. Regardless of duration of thermal stress, the localization of ABCG2 protein had no change. Moreover, heat stress also did not affect (P ＞ 0.05) the IOD of the ABCG2 positive portion and the expression of the ABCG2 mRNA in the pectorales, crureus, duodenum, jejunum, ileum and spleen, while significantly increased (P ＜ 0.05) the corresponding tissues ROS production at the end of the 1st week of heat stress. In contrast, at the end of the 2nd week of heat stress, IOD of the ABCG2 positive portion and the expression of the ABCG2 mRNA in heat stress group significantly increased (P ＜ 0.05), while the corresponding tissues ROS production had no difference (P ＞ 0.05) compared to the control group. Collectively, duration of thermal stress affects growth performance, serum oxidative stress indices, and the expression of ABCG2 and the ROS production of broiler tissues in a time-dependent manner. There is a negative correlation between the expression of ABCG2 and the ROS production in the corresponding tissues under heat stress. Graphical abstract: Image 1 Highlights: The duration of thermal stress affects growth performance, and serum oxidative stress indices of broiler in a time-dependent manner. Regardless of duration of thermal stress, the localization of ABCG2 protein had no change. The duration of thermal stress affects the expression ABCG2 and the ROS production in a time-dependent manner. There is a negative correlation between the expression of ABCG2 and the ROS production in the corresponding tissues under heat stress.